Cerebral venous system and anatomical predisposition to high‐altitude headache. Issue 3 (26th February 2013) - Wilson, Mark H.; Davagnanam, Indran; Holland, Graeme; Dattani, Raj S.; Tamm, Alexander; Hirani, Shashivadan P.; Kolfschoten, Nicky; Strycharczuk, Lisa; Green, Cathy; Thornton, John S.; Wright, Alex; Edsell, Mark; et al.
<x xml:space="preserve">Abstract</x> Objective As inspired oxygen availability falls with ascent to altitude, some individuals develop high‐altitude headache (HAH). We postulated that HAH results when hypoxia‐associated increases in cerebral blood flow occur in the context of restricted venous drainage, and is worsened when cerebral compliance is reduced. We explored this hypothesis in 3 studies. Methods In high‐altitude studies, retinal venous distension (RVD) was ophthalmoscopically assessed in 24 subjects (6 female) and sea‐level cranial magnetic resonance imaging was performed in 12 subjects ascending to 5, 300m. Correlation of headache burden (summed severity scores [0–4] ≤24 hours from arrival at each altitude) with RVD, and with cerebral/cerebrospinal fluid (CSF)/venous compartment volumes, was sought. In a sea‐level hypoxic study, 11 subjects underwent gadolinium‐enhanced magnetic resonance venography before and during hypoxic challenge (fraction of inspired oxygen = 0.11, 1 hour). Results In the high‐altitude studies, headache burden correlated with both RVD (Spearman rho = 0.55, p = 0.005) and with the degree of narrowing of 1 or both transverse venous sinuses (r = −0.56, p = 0.03). It also related inversely to both the lateral + third ventricle summed volumes (Spearman rho = −0.5, p = 0.05) and pericerebellar CSF volume (r = −0.56, p = 0.03). In the hypoxic study, cerebral and retinal vein engorgement were correlated, and rose as the combined conduit score fell (a measure of venous outflow restriction; r = ‐0.66, p < 0.05 and r = −0.75, p < 0.05, respectively). Interpretation Arterial hypoxemia is associated with cerebral and retinal venous distension, whose magnitude correlates with HAH burden. Restriction in cerebral venous outflow is associated with retinal distension and HAH. Limitations in cerebral venous efferent flow may predispose to headache when hypoxia‐related increases in cerebral arterial flow occur. ANN NEUROL 2013;73:381–389